The impact of perceived negative supervisor gossip on employee emotional exhaustion: a moderated mediation model of impression management and task interdependence - Cheng, Sheng; Wang, Yumei; Kuo, Chien-Chih (Frontiers in Public Health, 2025)
Negative gossip is a common behavior in the workplace. However, little research focuses on the employee perception of negative supervisor gossip in workplace. This study proposes that employee perceived negative supervisor gossip is a stressor that may lead employees to try coping using impression management tactics but ultimately to experience emotional exhaustion. Data were collected from 406 full-time Chinese employees and assessed with a time-lagged design. The results show that employee perceived negative supervisor gossip has a significant positive relationship with impression management, and impression management is positively correlated to emotional exhaustion. Furthermore, impression management mediates the relationship between perceived negative supervisor gossip and emotional exhaustion. Finally, task interdependence moderates the direct and indirect effects among perceived negative supervisor gossip, impression management, and emotional exhaustion. This study also discusses the theoretical and practical implications for managers. Specifically, supervisors should minimize the frequency of negative gossip behavior, encourage self-actualization among employees, and provide employees with more collaborative tasks.